Purchase Intention in Hotel Mobile Applications: The Role of Perceived Price and Ease of Use - Prabawathi, Ni Kadek Nia; Pitanatri, Putu Diah Sastri; Pinaria, Ni Wayan Chintia (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2026)
As mobile applications become more widely used in the hospitality industry, the way customers look for information, make reservations, and choose hotel services has also changed. However, booking intentions through hotel mobile applications remain relatively low or fluctuate over time, despite providing competitive prices and convenient amenities. This situation highlights the importance of understanding the factors that influence customers’ intentions to make purchases when using hotel mobile applications. This study aims to examine how perceived price and perceived ease of use influence the purchase intentions of hotel mobile application users. This study was conducted using an approach structured questionnaires distributed to 100 respondents who were familiar with the THG Apps. The obtained data were through descriptive statistics and multiple linear regression analysis with the assistance of SPSS. The results indicate that perceived price and perceived ease of use both have a positive and significant effect on purchase intention, with perceived price showing a slightly stronger influence. The findings of this study are expected to provide practical insights for hotel management in developing mobile application strategies that can enhance customer engagement and encourage reservations